The Influence of Brand Image on Online Purchase Decisions for Scarlett Students of The Faculty of Economics, University of Nias - Diana Novita Baene; Idarni Harefa; Meiman Hidayat Waruwu; Fatolosa Hulu (Economics and Business Journal (ECBIS), 2026)
This research aims to examine and analyze the influence of brand image on the purchasing decisions of students at the Faculty of Economics, Nias University, in the context of online shopping. The background of this study stems from the rapid growth of e-commerce in Indonesia, which has significantly changed consumer shopping behavior, particularly among students who are highly adaptive to digital technology. In online shopping situations, where consumers cannot physically assess the product, brand image becomes one of the main factors influencing consumer trust, perceived quality, and confidence in making purchasing decisions. The type of research employed is quantitative research with a survey approach. The study population consisted of 1,959 active students of the Faculty of Economics, Nias University, with a sample of 95 respondents determined using the Slovin formula. Data were collected using a Likert-scale questionnaire covering brand image indicators (strength, favorability, and uniqueness of brand association) as well as purchasing decision indicators (problem recognition, information search, evaluation of alternatives, purchase decision, and post-purchase behavior). The data were analyzed using validity and reliability tests, simple linear regression analysis, t-test, and determination test with the aid of SPSS software. The results of the study indicate that brand image has a positive and significant effect on students' purchasing decisions in online shopping. This finding implies that the stronger the brand image, the higher the tendency of students to make online purchases. Therefore, companies or online businesses need to develop and strengthen their brand image through consistent marketing communication strategies, clear product information, and credible brand reputation to increase consumer loyalty and purchase intention.